Catheter-associated urinary tract infection: why do not we control this adverse event? - Écila Campos Mota; Adriana Cristina Oliveira
ABSTRACT Objective: To identify factors related to the occurrence of urinary tract infection associated with urinary catheter use. Method: A longitudinal, retrospective cohort study carried out by analyzing the electronic medical records of patients admitted to an intensive care unit of a high-complexity hospital from July 2016 to June 2017. Demographic and clinical data were analyzed by descriptive and analytical analysis. Results: The incidence density of urinary tract infection related to urinary catheter use was 4.8 per 1000 catheters/day, the majority (80.6%) with no indication for catheter use, and there was no prescription for insertion and/or maintenance in 86.7%. The mean time between catheter insertion and infection diagnosis was 11.3 ± 6.3 days (6 to 28 days). Statistically significant factors (p < 0.001) related to urinary infection linked to catheter use were hospitalization time in the unit (16.7 ± 9 days), catheter permanence time (12.7 ± 6.9 days), and the use of antimicrobials in the intensive care unit (8.6 ± 6.3 days). Conclusion: The association of indication absence and the record of the need for maintenance possibly potentiated the occurrence of urinary tract infection associated to catheter use.